Damping and fretting of frictional contacts in the steady-state - Cwiekala, N (2022)
Contacts in mechanical assemblies are often subject to a constant load together with an oscillatory component. The latter might originate from vibration such that the component experiences a high number of load cycles. Different dissipative processes affect the steady-state behaviour of the assembly. In terms of contacts the most apparent is friction along the interface, which might lead to surface damage. Locally, the contact might act as a stress raiser, such that the material in the neighbourhood experiences plastic deformation. Cracks nucleating from the damaged surface and propagated in each load cycle are another limiting factor for the component's life. All these effects can be studied individually, but in reality they will affect each other to a certain degree. After a review of analytical and asymptotic contact descriptions, this thesis aims to describe the interaction between interfacial slip and other dissipative or life-limiting effects. A graphical method is presented to determine if a given loading causes the material in the contact region to reach the onset of plasticity. The limits of the elastic regime are explored and evaluated with this method.